Boy soldier of the Confederacy : the memoir of Johnnie Wickersham - Wickersham, John T., 1846-1916 (Southern Illinois University Press, 2006)
Presents a narrative that provides a look into the Civil War through the eyes of young fourteen-year-old Johnnie Wickersham, who wrote his memoirs fifty years after the war at the urging of his children and grandchildren.